Analisis Performansi Routing Protocol OLSR Dan AOMDV Pada Vehicular Ad Hoc Network (VANET) - Anisia, Rianda; Munadi, Rendy; Negara, Ridha Muldina (Jurusan Teknik Elektro Universitas Andalas, 2016)
Vehicular Ad-Hoc Network (VANET) is a development of the Mobile Ad-Hoc Network (MANET), which makes the vehicle as its nodes. VANET technology is expected to improve the security of drivers while driving on a highway between the others, with the map location, traffic information, warning if there will be a collision, and internet access in the vehicle. However, VANET has the characteristics of a network rapidly changing due to the rapid movement of nodes that need to have a routing protocol that is considered suitable and efficient so that data transmission can be optimally lasts. This research will be simulated and analyzed the comparative performance of Optimized Link State Routing Protocol (OLSR) and Ad Hoc On-demand Multipath Distance Vector (AOMDV) using urban conditions (urban). The environment will be tested in speed changes and the effect of the number of nodes nodes. This simulation was done using NS-equipped with SUMO 0.12.3 2:34. as mobility MOVE as a script generator and generator Performance was measured using parameters such as Average throughput comparison, Packet Delivery Ratio, Average End-to-end delay, Normalized Routing Load, and Routing Overhead. Results of analysis in environmental VANET, routing protocols AOMDV superior routing protocol than OLSR. Because almost all parameters tested in scenarios of changes in the number of nodes and node speed AOMDV have better performance so AOMDV more efficient use on urban environmental conditions.Keywords : VANET, NS-2, OLSR, AOMDV, SUMO, MOVEAbstrak— Vehicular Ad-Hoc Network (VANET) merupakan pengembangan dari Mobile Ad-Hoc Network (MANET) yang menjadikan kendaraan sebagai node nya. Teknologi VANET diharapkan dapat meningkatkan keamanan pengemudi saat berkendara di jalan raya antara lain dengan adanya map location, informasi lalu lintas, peringatan jika akan terjadi tabrakan, dan akses internet pada kendaraan. Namun, VANET memiliki karakteristik jaringan yang cepat berubah karena pergerakan node yang cepat sehingga perlu dipilih protokol routing yang dinilai cocok dan efisien sehingga pengiriman data dapat berlangsug secara maksimal. Pada penelitian ini akan disimulasikan serta dianalisis perbandingan kinerja Optimized Link State Routing Protocol (OLSR) dan Ad Hoc On demand Multipath Distance Vector (AOMDV) menggunakan kondisi urban (perkotaan). Di lingkungan tersebut akan diuji perubahan kecepatan node dan pengaruh jumlah node. Simulasi ini dilakukan dengan menggunakan NS-2.34 dilengkapi dengan SUMO 0.12.3. sebagai mobility generator dan MOVE sebagai script generator Performansi diukur menggunakan parameter perbandingan berupa Average throughput, Packet Delivery Ratio, Average End-to-end delay, Normalized Routing Load, dan Routing Overhead. Hasil analisis di lingkungan VANET, protokol routing AOMDV lebih unggul dibandingkan protokol routing OLSR. Karena hampir pada semua parameter yang diujikan pada skenario perubahan jumlah node maupun kecepatan node AOMDV memiliki performansi yang lebih baik sehingga AOMDV lebih efisien digunakan pada kondisi lingkungan perkotaan.Kata Kunci : VANET, NS-2, OLSR, AOMDV, SUMO,MOVE